Characterization of a novel protease from Bacillus cereus and evaluation of an eco-friendly hydrolysis of a brewery byproduct - Kotlar, Catalina Elena (2015)
Proteases and proteolytic enzymes constitute one of the most important groups of enzymes and are attracting worldwide attentionin attempts to exploit their physiological and biotechnological applications. In this study, partial purifications and biochemicaland antimicrobial characterizations of a protease from Bacillus cereus spp., originally isolated from fermented cabbage, werecarried out. The crude extract obtained after purification, involving ammonium sulphate precipitation and dialysis, was designatedas a partially purified protease (PPP). The obtained PPP had a specific activity of 0.395?2.539 U/g at 32 °C, with maximumactivities for the fractions precipitated at 60 and 80% ammonium sulphate. The PPP activity ranged between 20 and 55 °C, withan optimum temperature at 40 °C. At 60 °C, the PPP retained more than 30% of its activity. The optimum pH for the PPP wasachieved at pH 9, indicating the alkaline source of the enzyme. Protease production was specifically dependent on the calciumconcentration in the culture medium. Also the robustness of the protease on brewer?s spent grain hydrolysis was demonstrated.This suggests a potential eco-friendly application of the enzyme. Finally, it was found that the PPP inhibited the growth ofEscherichia coli O157:H7. This novel property of the PPP liberated by the B. cereus spp. could provide important future benefitsto industry.